‘The March Is Not Ended’: ‘Church’ Confronting the State over the Zimbabwean Crisis - Molly Manyonganise (Religions, 2022)
The Zimbabwean crisis has been on-going since the year 2000. The various ecumenical bodies of the church in Zimbabwe have been voicing their concerns to the state through meetings and pastoral letters. While the church has been touted as a critical player in conflict resolution and peacebuilding, concerns about the church have been raised. One of these has been the issue of a divided organization that has failed to speak with one voice. With the coming into power of the so called ‘Second Republic’, hopes were raised that the state would be willing to have the crisis resolved. However, the crisis has just worsened, and the church has again been forced to break its silence. The purpose of this paper is to analyse the pastoral letter that was issued by the Zimbabwe Catholic Bishops Conference on 14 August 2020, titled ‘The March is not Ended’, which sought to respond to the crisis in Zimbabwe. The paper seeks to establish what religious groups can achieve in the event that they set aside their differences for the common good in conflict situations. Data for the paper were gathered through the issued pastoral letter, as well as the responses to it on online media.